Assessment of isokinetic strength of knee extension/flexion of individuals with intellectual developmental disabilities: Systematic review with protocol proposal - Jacinto, M.; Caseiro, A.; Antunes, R.; Monteiro, D.; Campos, M. J.; Matos, R.; Ferreira, J. P.; Gomes, B. (Strength and Conditioning Journal, 2025)
Muscle performance is a crucial determinant of physical function in the daily lives of individuals with intellectual developmental disabilities (IDD), with lower strength levels often leading to loss of independence. The isokinetic dynamometer has been established as a reliable method for assessing muscle performance in this population. This article outlines the design of a protocol to be adopted to assess isokinetic knee strength in individuals with IDD. Using systematic review methodology, electronic searches were conducted in PubMed, Scopus, SPORTDiscus, and Web of Science databases, including articles published between January 1990 and September 2022. The key terms were combined with the Boolean operator "AND" or "OR". After the methodological process, 23 studies were included for analysis. The protocol proposal consists of 8 phases, covering previous considerations: (a) warm-up, (b) familiarization; (c) equipment adjustment, choosing the limb to evaluate and in what type of action (concentric and/or eccentric); (d) number of repetitions and sets; (e) the rest duration; (f) angular velocity to be tested; and (g) parameters for analysis. It is intended that this article provide insights into the development of a useful tool for the various stakeholders interested in assessing the isokinetic knee strength of individuals with IDD.